Assessment of the implementation of a national patient safety alert to reduce wrong site surgery. Issue 6 (8th December 2008) - Rhodes, P; Giles, S J; Cook, G A; Grange, A; Hayton, R; Maxwell, M J; Sheldon, T A; Wright, J
Abstract : Background: In 2005, guidance on how to prevent wrong site surgery in the form of a national safety alert was issued to all NHS hospital trusts in England and Wales by the National Patient Safety Agency. Objective: To investigate the response to the alert among clinicians in England and Wales 12–15 months after it had been issued. Methods: A before–after study, using telephone/face-to-face interviews with consultant surgeons and senior nurses in ophthalmology, orthopaedics and urology in 11 NHS hospitals in England & Wales in the year prior to the alert and 12–15 months after. The interviews were coded and analysed thematically. Results: The study revealed marked heterogeneity in organisational processes in response to a national alert. There was a significant change in surgeons' self-reported practice, with only 48% of surgeons routinely marking patients prior to the alert and 85% after (p<0.001). However, inter-specialty differences remained and change in practice was not always matched by change in attitude. Compliance with the detailed recommendations about how marking should be carried out was inconsistent. There were unintended consequences in terms of greater bureaucracy and concerns about diffusion of responsibility and hastily performed marking to enable release of patients from wards. Conclusion: The alert was effective in promoting presurgical marking and encouraging awareness of safety issues in relation to correct site surgery. However, care should be taken to monitor unintended consequences and whether change is sustained. Greater flexibility for local adaptation coupled with better design and early testing of safety alerts prior to national dissemination may facilitate more sustainable changes in practice.